1979
DOI: 10.1079/bjn19790085
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of vitamin C from the human buccal cavity

Abstract: I . Ascorbic acid was absorbed across the mucosa of the human mouth. 2. Omission of sodium ions from the medium decreased the absorption of ascorbic acid. 3. The presence of D-glucose, or 3-O-methyl-~-ghcose, increased the absorption of ascorbic acid but 4. Calcium ions also increased ascorbic acid absorption probably by a secondary effect on Na+ fluxes. 5. Buccal mucosa was also permeable to dehydroascorbic acid and D-isoascorbic. acid D-fructose had little effect and D-mannitol had no effect.Investigations u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Ascorbate anion is only 1.6% unionized at pH 6, this was the pH at which the buccal cavity was at the experiments when performed (Sadoogh and Evered, 1979). Furthermore, ascorbic acid is very soluble in water and poorly soluble in lipid.…”
Section: Absorption Of Ascorbic Acidmentioning
confidence: 96%
See 2 more Smart Citations
“…Ascorbate anion is only 1.6% unionized at pH 6, this was the pH at which the buccal cavity was at the experiments when performed (Sadoogh and Evered, 1979). Furthermore, ascorbic acid is very soluble in water and poorly soluble in lipid.…”
Section: Absorption Of Ascorbic Acidmentioning
confidence: 96%
“…It was also shown that the process was not stereo specific since the natural form, L-ascorbic acid, and unnatural D-isomer were transferred across buccal mucosa at similar rate. The absorption of the vitamin is not sex dependent and the absorption of ascorbic acid did not reach a maximum with increasing concentration of up to 20 M (Sadoogh and Evered, 1979). The transportation of vitamin C across the buccal mucosa was found to be enhanced by glucose; it was then taught that glucose provides an energy metabolite (Sadoogh and Evered, 1979).…”
Section: Absorption Of Ascorbic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcellular route (passing through the cell): The transport of food sugars across human buccal mucosa shows proven stereospecifity. For the natural isomers D-glucose and D-galactose the transport is at least partly sodium-dependent 8,9 . The presence of a specialized sodium ion dependent transport mechanism for D-glucose was found in the dorsum of the tongue and (with slower absorption) from the ventral surface of the tongue 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…When dealing with oral mucosal tissues, vitamin C is easily absorbed by passive diffusion through the buccal mucosa [14]. It was found that the absorption of the ascorbic acid through the buccal mucosa and small intestine is nearly equal [120].…”
Section: Topical Route and Topical Formulationsmentioning
confidence: 99%